3. DETENTION OF FOREIGN NATIONALS IN THE SEMARANGBANGLADESHI FAKE VISA CASE AS AN IMPLEMENTATION OFIMMIGRATION LAW ENFORCEMENT IN INDONESIA - Virda Anika Wahyuni; Nur Priyanto; Suroso; Anwar Hendro; Hendri Himawan; Tutidikatama; Muchammad Furqon (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to analyze detention practices regarding foreign nationals (WNA)in the case of a forged visa used by Ruhilul Amin, a Bangladeshi national who enteredIndonesia using documents inconsistent with immigration databases; the discrepancy was onlydetected when he applied for a residence permit extension at the Class I Special ImmigrationOffice (TPI) in Semarang. Findings indicate that multi-layered administrative checks—includingvisa code verification, document metadata analysis, and biometric screening—served as theprimary mechanisms for identifying data mismatches that pointed to suspected documentforgery. The study also highlights the pivotal role of